ANALISIS PENGGUNAAN ALOKASI DANA DESA (ADD) DALAM PEMBERDAYAAN MASYARAKAT DI DESA SOLEWATU KECAMATAN TINONDO KABUPATEN KOLAKA TIMUR - Wahyuni Wahyuni; M.Askari Zakariah; Nurhayati Nurhayati (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Village Fund Allocation (ADD) is in order to increase empowerment, welfare and equitable development in rural areas through district, provincial and central government APBD funds, district, provincial and central governments need to realize APBD funds of 10% each for Village Fund Allocation (ADD) ).The formulation of the problem in this study is how the use of Village Fund Allocation (ADD) in Solewatu Village, Tinondo District, East Kolaka Regency towards community empowerment The research objective is to find out how the use of Village Fund Allocation (ADD) in Solewatu Village, Tinondo District, East Kolaka Regency towards empowerment Public.The research method used is a qualitative approach with this type of descriptive research. The research procedure carried out includes the observation, interview and documentation stages. The instruments used in researching are interview guidelines, observation guidelines, as well as photos and voice recorders which are documentation media. As for data analysis techniques used are data reduction, data presentation, drawing conclusions, and testing the validity of the data.The results showed that the use of village fund allocations in Solewatu Village, Tinondo District, East Kolaka Regency has been carried out based on the applicable rules or laws and is in accordance with the concept of mandate. Village Fund Allocation (ADD) in Desa Solewatu Kec. Tinondo Kab. East Kolaka Rp. 372,970,000, - used in empowering the community as well as physical development and non-physical development. For community empowerment, a village fund allocation (ADD) of Rp. 32,000,000, - which is channeled to increase the capacity of village heads and officials as well as training / counseling for women's empowerment. Whereas for physical and non-physical development using the village fund allocation (ADD) of Rp. 340,970,000, - which is distributed in the field of village administration and village community development